Hotspots of mite new species discovery: Trombidiformes (2013–2015) - Liu, Jian-Feng; Zhang, Zhi-Qiang (Zootaxa, 2016)
This paper reveals the hotspots of new mite discovery through of a survey of type localities of new Trombidiformes species described in two journals (Systematic & Applied Acarology and Zootaxa) during the last three years (2013–2015). Taxonomically, the 491 new species of the Trombidiformes are highly unevenly distributed among 55 families with top 10 families accounting for over 66% of the total. The Eriophyidae is the top-ranked family. Geographically, these 491 new species are from 55 countries around the world and their distribution among the countries is highly uneven. The majority of these new species (69%) are from the top 10 countries and six of the top ten countries are also megadiversity countries. The top three countries are all from Asia (Iran, China and Malaysia) and they together accounted for over one third of all new species of the Trombidiformes described in the two journals during 2013–2015.